2023
DOI: 10.1002/smll.202300762
|View full text |Cite
|
Sign up to set email alerts
|

Toward the High‐Performance Lithium Primary Batteries by Chemically Modified Fluorinate Carbon with δ‐MnO2

Abstract: Li/CFx battery is one of the most promising lithium primary batteries (LPBs) which yields the highest energy density but with poor rate capability. This Achilles'’ heel hinders the large‐scale applications of Li/CFx batteries. This work first reports a facile chemical modification method of CFx with δ‐MnO2. Having benefited from the chemical bonding, the electrochemical performance at high‐rate discharge is remarkably enhanced without compromising the specific capacity. The coin cells exhibit an energy density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…The 19 F spectra of the fluorinated CNFs before and after milling are shown in Figure 4c. Whatever the sample, the fine peak centered at −187 ppm is assigned to the covalent C-F bonds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 19 F spectra of the fluorinated CNFs before and after milling are shown in Figure 4c. Whatever the sample, the fine peak centered at −187 ppm is assigned to the covalent C-F bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The 19 F and 13 C solid-state NMR experiments were performed using a 300 MHz Bruker Avance spectrometer at room temperature. A cross-polarization (CP)/magic-angle spinning (MAS) NMR probe operating with 2.5 mm and 4 mm rotors was used at 30 kHz and 10 kHz spinning rates for the 19 F and 13 C measurements, respectively. A probe (Bruker) with fluorine decoupling on a 4 mm rotor was used.…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with previously reported CFx cathodes, the FCNH-160 cathodes in this study showed unprecedented rate capabilities (Figure 6f; Table S3, Supporting Information). [11,15,30,35,[40][41][42][43][44] The relatively poor rate capability of FCNH-160 is attributed to the poor electrical conductivity, which decreases from 1.05 × 10 4 S cm −1 for pristine CNH to 3.57 × 10 −9 S cm −1 after the fluorination process. The drastically reduced electrical conductivity was assigned to the destruction of conjugated structure, revealed by the few remaining sp 2 hybridized C atoms in the XPS spectrum.…”
Section: Resultsmentioning
confidence: 99%